Zernaki Tepe: an Artaxiad hippodamian city in Greater Armenia - Dan, Roberto (ARAMAZD: Armenian Journal of Near Eastern Studies, 2019)
This article is focussed on the analysis of a very intriguing site located today in modern Turkey, Zernaki Tepe, one of the most interesting and debated in this region. The main feature of the site is its distinctive inhabited area, which is considered to be one of the oldest examples of a city with urban planning based on a Hippodamian Model. In the present article an archaeological review and some chronological hypothesis are offered. A first Urartian period occupation of Zernaki Tepe is highly possible, as attested by some specific rock-cut features and possible pottery evidence. Most of the remains currently visible on the site, the grid plan, and the remnants of important buildings featuring columns and stucco, point more realistically to the Artaxiad period, which was influenced by Hellenistic/Seleucid – Parthian period architecture.